Prevalence of metabolic dysfunction-associated fatty liver disease and its association with physical function in patients with acute coronary syndrome. (11th May 2022) - Noda, T; Kamiya, K; Hamazaki, N; Nozaki, K; Ichikawa, T; Yamashita, M; Uchida, S; Maekawa, E; Yamaoka-Tojo, M; Matsunaga, A; Ako, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): JSPS KAKENHI Background: It is widely known that patients with acute coronary syndrome (ACS) are at increased risk of nonalcoholic fatty liver disease (NAFLD), which is linked to sarcopenia and physical dysfunction. However, the relationship between metabolic dysfunction-associated fatty liver disease (MAFLD) and physical dysfunction remains unclear. Purpose: The purpose of this study was to investigate the prevalence of MAFLD in patients with ACS to assess the relationship between MAFLD and muscle strength, walking speed, and 6-minute walking distance (6 MWD). Methods: We reviewed patients with ACS who were assessed for hepatic steatosis using the fatty liver index, and the results were further assessed to determine the presence of MAFLD. Multiple regression analysis was used to examine the association between MAFLD and physical function. Results: Among 479 enrolled hospitalized patients, MAFLD was identified in 234 (48.9%) patients. We conducted a multiple regression analysis in which MAFLD was independently associated with lower leg strength, gait speed, and 6 MWD (leg strength, P = 0.023; gait speed, P = 0.002 and 6 MWD, P = 0.017). Furthermore, having more metabolic impairment was still associated with lower physical function decline (leg strength, P for trend = 0.002; gait speed, P for trend = 0.019 and 6 MWD, P for trend = 0.003). Conclusions: MAFLD is common in hospitalized patients with ACS, and most patients with MAFLD have many overlapping metabolic abnormalities. MAFLD is associated with impaired physical function, and the greater the number of overlapping metabolic abnormalities, the worse the motor function.